Politik Tata Kelola Sumber Daya Alam di Era Reformasi: Jejaring Elite, Konflik Kepentingan, dan Ketimpangan Ekologis - Ahmad Sholikin (Universitas Islam Darul Ulum Lamongan, 2025)
The post-1998 political transition in Indonesia was expected to democratize natural resource governance. However, the current reality demonstrates a paradoxical shift towards centralized oligarchic control, culminating in the enactment of the Job Creation Law (UU Cipta Kerja). While existing literature often separates macro-legal critiques from micro-level project failures, this article integrates political economy and political ecology perspectives to examine how legal architecture systematically manufactures ecological inequality. Employing a qualitative documentary research method, this study analyzes legal frameworks and investigative reports from various civil society organizations. The findings reveal three interconnected mechanisms of exploitation. First, UU Cipta Kerja functions as an oligarchic legal architecture that facilitates regulatory capture, systematically dismantling environmental safeguards and public participation. Second, the implementation of the National Strategic Project of Food Estate in Central Kalimantan operates as an arena for rent-seeking, where the narrative of national food security disguises state-sponsored resource grabbing and massive deforestation. Third, the timber extracted from this deforestation is integrated into the global supply chain of transnational pulp industries, utilizing greenwashing mechanisms to penetrate strict international markets, including the European Union. Ultimately, this study concludes that ecological degradation at the grassroots level is not a mere administrative failure, but a deliberately manufactured outcome that privatizes wealth for the elite network while burdening Indigenous and local communities with permanent socio-ecological vulnerabilities.